Bridges or Barriers? The Relationship between Immigrants' Early Labor Market Adversities and Long-term Earnings. Issue 4 (December 2021) - Zhang, Tingting; Banerjee, Rupa
Using data from the Extended Longitudinal Survey of Immigrants to Canada (LSIC-IMDB), this article investigates the association between early adverse labor market experiences in the host country and immigrants' long-term earnings. We use Growth Curve Modeling (GCM) to estimate how months of joblessness, part-time status, and occupational mismatch during the first four years in Canada relate to immigrant men's and women's earnings trajectories over the following 10 years. Part-time employment, we find, is negatively associated with long-term earnings trajectories for both male and female immigrants, and male immigrants who are occupationally mismatched in the medium term also face a long-term wage penalty. Months of joblessness early on, however, is associated with relatively less wage disadvantage in later years. Since immigrants' early difficulties are associated with long-term economic scarring, it is imperative to introduce early interventions to promote rapid assimilation.